The Effect of Free Cash Flow, Size, and Growth with Profitability as Moderating Variable on Earning Response Coefficient in Property Sector - Wiwit Irawati (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
This thesis is a quantitative research market based accounting research manifold explanatory causality which aims to analyze and prove the influence of Free Cash Flow, Size, and Growth with Profitability moderated to Earning Response Coefficient on Property Sector. In an efficient market, the published financial information will be responded promptly by the market in this study is proxied by the ERC. Data obtained from the Indonesia Stock Exchange and is compliant with the classical assumption, as normality test, multicollinearity test, heteroscedasticity test, and test of auto correlation. The results of the data with SPSS version 22 obtain the adjusted R squared of 0.297 with a significance level of 0.027 <0.05. Then the hypothesis is accepted Free Cash Flow, Size, and Growth with Profitability moderated negative influence on Earning Response Coefficient on Property Sector with great influence 29.7%. The relationship is negative, which means that signaling theory that happens is bad news.